Production and Exchange Rate Impact on Indonesian Industrial Exports Goods - Francisca Sestri Goestjahjanti; Betharia Efriani; Winanti Winanti; Rahmawati Rahmawati; Istajib Kulla (Economics Development Analysis Journal, 2023)
The Indonesian consumer goods industry has been stagnant for four years 2014 – 2018 with the export average of only 5.5 trillion or equivalents to zero % growth. Since the government has been working hard for economic recovery during Covid 19 pandemic, the growth has grown to 20 trillion in 2021 (after the pandemic). Therefore, this research aimed to describe the influence of production and exchange variables on export growth of consumer goods industry in Indonesia. It used a linier regression method by using quarterly time series data of 2008 – 2021 which have been never studied before. The result showed that there found 78.80 % increase of export (cateris paribus) for 1 % production increase, 41.80 % increase of export for 1 % exchange rate increase, and 1 % of production and exchange rates increases caused 81.90 % increase in exports. Based on the explanation, there found a positive and significant effects between production and exchange rates on the export of consumer goods industry partially and simultaneously. It means that both factors are substantial and needed to be continuously improved in order to increase the export value of Indonesian consumer goods industry which in the end will also have positive impact on its growth.